Differential outcomes of TLR2 engagement in inflammation‐induced preterm birth. Issue 3 (28th December 2017) - Cappelletti, Monica; Lawson, Matthew J.; Chan, Calvin C.; Wilburn, Adrienne N.; Divanovic, Senad
Abstract: Preterm birth (PTB) is the leading cause of neonatal mortality worldwide. Infection and inflammation are considered main causes of PTB. Among multiple pathogens, Gram‐positive bacteria are commonly linked with induction of PTB. Although activation of innate immune responses, via TLR2 engagement, by Gram‐positive bacteria is a likely cause, whether induction of PTB depends on the potency of specific microbial components to induce Toll‐like receptor (TLR)2‐driven inflammation has not been elucidated. Here, we show that TLR2 activation by synthetic lipopeptides, Pam2Cys, and Pam3Cys specifically, variably influenced inflammation and subsequent induction of PTB. Pam2Cys challenge, compared to Pam3Cys, induced PTB and promoted significantly higher expression of inflammatory cytokines, specifically IL‐6 and IFN‐β, both in vivo and in vitro . Notably, antibody‐mediated neutralization of IL‐6 or genetic deletion of type I IFN receptor (IFNAR) was sufficient to protect from Pam2Cys‐driven PTB and to temper excessive proinflammatory cytokine production. Conversely, IFN‐β or IL‐6 was not sufficient to promote induction of PTB by Pam3Cys. In summary, our data implies a divergent function of TLR2‐activating lipopeptides in the magnitude and type of ligand‐driven inflammatory vigor in induction of PTB.